MENGKAJI PANDEMI COVID-19 DALAM PERSPEKTIF MASYARAKAT RISIKO - Audina Rismayanti Fadlillah; Assyfa Wahida Rachman; Nur Cholifah (CV. ADIBA AISHA AMIRA, 2023)
The COVID-19 pandemic has become a global disaster that affects not only global health, but also all aspects of life including social, economic, political and cultural, religious and educational. This places society in a situation that is fraught with risk. This does not mean that all aspects of life are at risk, but life is always marked by various risks that affect the process of society. This article tries to examine the Covid-19 pandemic from the perspective of the sociology of the risk community. The Covid-19 pandemic has also shown that countries are truly unprepared. This is reflected in the state's difficulties in managing public discipline and accountability, as well as demonstrating their unpreparedness to deal with vulnerable communities. With that in mind, the state needs risk management in a dynamically complex society.